Ask questions and get helpful answers.

Starting with F(x) = integral (-2, x) 3t^2(cos (t^3) + 2) dt, use substitution u(t)=t^3 to rewrite the definite integral. You should get a new equivalent expression for F(x), which consists of this new definite integral.

  1. 👍
  2. 👎
  3. 👁
  4. ℹ️
  5. 🚩

1 answer

  1. u = t^3
    so t = u^(1/3)
    du = 3 t^2 dt
    so dt = du/3 t^2 = du /3u^(2/3)
    if t = -2 , u = -8
    if t = x, u = x^3

    1. 👍
    2. 👎
    3. ℹ️
    4. 🚩

Answer this Question

Related Questions

Still need help?

You can ask a new question or browse existing questions.